Reconstructing the Colonial Discourse: Malay Seafarers, Power, and the Rewriting of Maritime History - Amin, Ahamad Jama' (Melayu: Jurnal Antarabangsa Dunia Melayu, 2025)
This article interrogates the colonial discursive construction that categorised Malay seafarers as pirates in the maritime historiography of Southeast Asia—a label laden with political prejudice and deployed as a hegemonic epistemic tool to undermine indigenous sovereignty. Anchored in this critical issue, the study aims to uncover the latent power structures embedded within colonial rhetoric and to examine how the notion of piracy functioned as a discursive strategy to delegitimise Malay maritime authority. This article employs a critical discourse analysis of colonial texts in comparison with traditional Malay sources, such as the Sejarah Melayu and Hikayat Hang Tuah. It examines how colonialism functioned not only through spatial domination but also through a systematic colonisation of meaning. The findings reveal that Malay seafarers were not anarchic actors as often portrayed; rather, they were legitimate executors of state sovereignty, situated within a regional political ecosystem governed by indigenous customs, royal protocol, and cosmological values. This study highlights the urgent need to reconstruct maritime history in the Malay world through the lens of indigenous epistemology, repositioning seafarers as sovereign agents and custodians of national honour. This shift in perspective is imperative not only for restoring historical justice but also for reclaiming intellectual sovereignty from established colonial viewpoints. Full text: PDF